Correlation Between brGDGTs Distribution and Elevation From the Eastern Qilian Shan - Wang, Hansheng; Gao, Peng; Yang, Rui; Nie, Junsheng; Cao, Bo; Zhou, Aifeng; Pan, Baotian; Chen, Lin; Peng, Tingjiang (Frontiers in Earth Science, 2022)
A clear understanding of the uplift history of the Tibetan Plateau is the key for correctly understanding its uplift mechanisms and impacts on the Asian environment. However, consensus has not been reached regarding the uplift history of the Tibetan Plateau, especially because of lack of well-calibrated paleoaltimetry proxies and lack of knowledge of how to correctly apply them to the past. Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are a promising paleoaltimetry proxy because these large molecules tend to get preserved in sediments, and this proxy has a clear relationship with mean annual air temperature (MAAT), circumventing convoluted impact of precipitation or isotope variations on isotope-based paleoaltimetry proxies. As a result, many calibrations have been carried out linking brGDGTs with paleoelevation. Qilian Shan of the northeastern Tibetan Plateau is a key place testing previous models regarding the uplift model of the Tibetan Plateau. However, no modern calibration equation linking brGDGTs with MAAT is available. Here, we presented the first calibration equation between brGDGTs and MAAT from the eastern Qilian Shan with an elevation ranging from 2,055 to 3,300 m [MAAT = −15.50 + 49.55 × MBT′5ME (R2 = 0.89, p < 0.001, RMSE = 1.07°C)]. We further established the calibration between MBT′5ME-derived MAAT and elevation. This dataset lays the foundation to understand the uplift history and environmental variations of the northeastern Tibetan Plateau area.